Impacto deletéreo del síndrome coronario agudo en la independencia del adulto mayor - Coello, Paul (2025)
Objectives. To evaluate the prognostic role of functional status in older adults hospitalized for acute coronary syndrome (ACS) and the implications of the coronary event on functional decline during follow-up. Materials and methods. This was a single-center, prospective cohort study including patients aged ≥65 years hospitalized for ACS with (STEMI) or without ST-segment elevation in 2022. Patients with total dependence or lacking a care network were excluded. Functional status was assessed using the Barthel Index and the Lawton and Brody scales at admission, 30 days, and one year post-discharge. The association between initial functional status and major adverse cardiovascular events (MACE) was analyzed, as well as the impact of ACS on functional status over the short and long term. Results. A total of 110 patients older than 65 years were included (mean age 78.8±4.6 years; 61.8% male). At admission, 94.3% presented mild functional dependence according to the Barthel Index, with similar findings on the Lawton and Brody scales. At 30 days, a significant functional decline was observed (Barthel: 71.2±11.3, p<0.001; Lawton: 4.8±2.5, p=0.02), which persisted at one year. Initial functional status was not associated with MACE. ST-segment elevation ACS (STEMI) was an independent predictor of short-term functional decline (adjusted OR 1.75; p=0.04). Conclusions. In older adults with ACS, initial functional status did not predict adverse events; however, significant functional decline was observed, particularly after STEMI. This underscores the importance of personalized strategies for managing this vulnerable population.